Vacinação com Escherichia Coli j5 no período pré-parto e ocorrência de mastite, produção de leite e desempenho reprodutivo de vacas mestiças leiteiras - Patricia Vieira Maia (2011)
The effect of immunization with Escherichia coli J5 vaccine in the pre-partum on the occurrence of mastitis, milk production and reproductive performance in crossbred dairy cows was evaluated. The prevalence of coliform intramammary infections at postpartum, occurrence and duration of clinical cases of mastitis, somatic cell count, milk production, number of animals inseminated and pregnant in the first 100 days of lactation and the conception rate to first service were analyzed. Ninety-three cows were used and distributed in two experimental groups, as follows: forty-three cows in the vaccinated group and fifty cows in the unvaccinated group. Immunizations occurred 15 days before the scheduled date of dry off, at dry off and 15 days after dry off. On the day of drying and seven days after calving milk samples were collected for microbiological diagnosis of mastitis. The occurrence of clinical mastitis cases was confirmed by visible changes in milk using the strip cup test during milking. The duration and intensity of these cases were evaluated. Milk samples for somatic cell count (SCC) were collected monthly from the day 10 to 100 of lactation. Milk production was recorded monthly for the first 100 days of lactation. The estrus detection was done by trained employee three times a day after 40 days postpartum. Pregnancy check was performed 35 days after insemination. There was no reduction in the prevalence of infections caused by coliforms between drying-off and parturition in both groups (p>0,05). The total duration of clinical mastitis in animals with clinical mastitis was lower in vaccinated (p<0,05) than unvaccinated cows. The number of clinical episodes and intensity of clinical cases did not differ between groups (p>0,05). The prevalence of animals with subclinical mastitis at postpartum and SCC in the first 100 days of lactation were lower in vaccinated (p<0,05) than unvaccinated cows. However, there was no difference in milk production between groups (p>0,05). The conception rate at first service and the number of pregnant animals up to 100 days of lactation did not differ between groups (p>0,05). However, animals with clinical mastitis had a lower conception rate and also a lower number of animals pregnant (p<0,05) than health animals. The number of animals inseminated up to 100 days of lactation did not differ between groups and between animals that had clinical episodes of mastitis (p> 0,05). Vaccination of cows with E. coli J5 improves mammary gland health by reducing the prevalence of animals with subclinical mastitis at postpartum, as well as the duration of the clinical cases of mastitis and somatic cell count in the drying and the first 100 days of lactation. Milk production, the occurrence of clinical cases of mastitis in the first 100 days of lactation and the reproductive efficiency are not altered by use of the vaccine E. coli J5